FAKTOR-FAKTOR YANG MEMPENGARUHI STRESS KERJA PADA PERAWAT AKIBAT BEBAN KERJA YANG TINGGI : LITERATUR REVIEW - Aisyah, Ratu Nur; Handayani, Sarah (J-KESMAS: Jurnal Kesehatan Masyarakat, 2023)
The level of work stress in the work environment can increase the risk of mental and physical health disorders in individuals, which can affect performance and overall well-being. The aim of carrying out this scientific study is to determine the factors that influence work stress in nurses due to high workload. The method used in the literature review was to analyze eight journals as references by applying PICO. The results show that from the eight scientific research studies, it was found that there was a correlation between high workload and stressful events experienced by nurses, where the higher the workload, the higher the level of stress experienced by nurses. Nurses have complexities in their work, from caring to communicating with patients and their families, so attention is needed from the hospital or employer to balance the workload and welfare of nurses in carrying out their professional duties.